Associations of event-related brain potentials and Alzheimer’s disease severity: a longitudinal study - Fruehwirt, W; Dorffner, G; Roberts, S; Gerstgrasser, M; Grossegger, D; Schmidt, R; Dal-Bianco, P; Ransmayr, G; Garn, H; Waser, M; Benke, T (Elsevier, 2018)
Background: So far, no cost-efficient, widely-used biomarkers have been established to facilitate the objectivization of Alzheimer’s disease (AD) diagnosis and monitoring. Research suggests that event-related potentials (ERPs) reflect neurodegenerative processes in AD and might qualify as neurophysiological AD markers.